Interleukin‐6 enhances the activity of in vivo long‐term reconstituting hematopoietic stem cells in "hypoxic‐like" expansion cultures ex vivo. Issue 11 (27th May 2015) - Duchez, Pascale; Rodriguez, Laura; Chevaleyre, Jean; Lapostolle, Veronique; Vlaski, Marija; Brunet de la Grange, Philippe; Ivanovic, Zoran
Abstract : BACKGROUND: Since interleukin (IL)‐6 synergizes with the physiologically relevant O2 concentration in the maintenance of primitive hematopoietic stem cell (HSC) subpopulations, we hypothesized that its addition to our hypoxic response mimicking cultures (HRMCs), composed of an antioxidant‐supplied serum‐free xeno‐free medium supplemented with the cytokines stabilizing hypoxia‐inducible factor‐1α and balancing HSC self‐renewal and commitment, will result in a similar effect even if they are exposed to 20% O2 . STUDY DESIGN AND METHODS: HRMCs were exposed to 20 and 5% O2 with and without IL‐6. Functional committed progenitors (colony‐forming cells [CFCs]: CFU‐GM, BFU‐E, CFU‐Mix, and CFU‐Mk) were evaluated as well as the short‐ and long‐term repopulating HSCs using in vivo NSG mice model (primary and secondary recipients, respectively). RESULTS: The addition of IL‐6 to HRMCs exposed to 20% O2 did not significantly impact either the CFCs or in vivo short‐term repopulating cells. However, it enhanced both the frequency and the individual proliferative capacity of the most primitive long‐term repopulating cell population evidenced by the generation of human CFCs in the marrow of secondary recipient mice. The exposure of HRMCs to 5% O2 negatively affected the amplification of CFCs, which was not changed by the addition of IL‐6 and exhibited a partial enhancing effect on the long‐term repopulating cells. CONCLUSION: The addition of IL‐6 to the cytokine cocktail further improves our expansion procedure based on atmospheric O2 concentration‐exposed HRMCs by enhancing the maintenance of the most primitive HSCs without a negative impact on the less primitive HSC populations and CFCs.